A Study Of The Agriculture Of Poland And Romania In Post-Communist Period - Laurentiu Ivanov (European Scientific Journal, ESJ, 2016)
In terms of size of territory and population, Poland and Romania are the largest former socialist countries, now, members of the European Union. In the last 25 years of transition to a market economy, Poland has excellent managed its natural potential and is, now, an economic model for other former socialist countries, including Romania. Poland has not experienced economic recession; its positive economic evolution was completely different from the evolution of the largest European economies, many of them facing distressful situations for long periods of time. The question to be addressed in this paper is: „How could we explain the present success of Polish agriculture? Could the present economic realities be partially influenced by the historical evolution of a country? “ In an attempt to provide an answer to this question, the present paper will highlight the economic developments in Romania and Poland in relation to developed countries for the last about 100 years in terms of “path dependency theory” and will conduct a comparative analysis between the two countries.